Towards a progressive economic development agenda for countries endowed with natural resources: Lessons from the rise and demise of the Bolivarian Revolution - Leonardo Vera Azaf (Cuadernos de Economía, 2025)
The purpose of this paper is to identify some of the new economic challenges faced by left-wing forces in Latin America, especially in countries endowed with natural resources. We propose a set of progressive policy responses to prevent the regional Left from repeating the missteps of the policy agenda followed by the so-called Bolivarian Revolution in Venezuela. We highlight the need to build an alternative based on what we call “progressive democratic development.” Our fundamental message is that the democratic Left has to overcome the misleading dichotomy that indicates that society is organized by the power of the state or the market. Instead prominence must be given to civil society. Several ideas are raised about how to work on the behalf of and lend prominence to civil society and the poorest segment of the population, particularly in the context of natural resource rich economies. The essay explores new formulas to manage mining and oil wealth, provide a social protection system to the growing informal sector, and to manage macroeconomic policy in a socially responsible manner.